Banten Plants and their Mapping in the Taman Gumi Banten Forest, Wanagiri Village, Sukasada-Buleleng - Wijana, Nyoman; Mulyadiharja, Sanusi; Riawan, I Made Oka (Undiksha, 2020)
The objectives of this study were: (1) to determine the benefits of plant species in the Taman Gumi Banten area based on local village wisdom. (2) produce maps of vegetation, general distribution of plants and offerings in their natural nature. This research is included in exploratory research. The locations of this research all took place in the forests of Taman Gumi Banten and the villages of Wanagiri, Sukasada, Buleleng. The population of this research is (a) Vegetation Mapping: the entire forest area of Taman Gumi Banten. (b) Social: The entire Wanagiri village community. Research samples: (a) Vegetation mapping: forest boundaries of Taman Gumi Banten. Social: Service Village 5 people, Traditional Village 5 people, Balian 2 people, Banten Tukang 5 people, Community Leaders 10 people, General public 50 people. Total 77 people. Sampling methods: (a) Vegetation mapping: total sampling. Social: Systematic sampling. Data collection methods: (a) Vegetation Mapping: Simple measurement technique. Useful Plants / Plants of Banten: quadratic method. Social: interviews, observations, and questionnaires. The results showed: (1) The plant species that make up the ecosystem in Taman Gumi Banten, Wanagiri Village consist of 67 species. The composition of the species of offerings in the forest of Taman Gumi Banten, Wanagiri village, consists of 25 species of plants that can be used as for making traditional offerings. Of the 25 species of banten plants, the body parts or plant organs used were 1 species (4.35%) of roots, 3 species of stems (13.04%), 9 species of leaves (39.13%), 4 species (17.39%), fruit as many as 8 species (34.78%), and 1 species used tuber parts (4.35%). Thus, the most widely used parts of the existing plants in the Gumi Banten forest to be used as infrastructure for offering materials are the leaves and fruits. (2) General plant vegetation map and Banten plant map have been produced.